View of Drogheda from the banks of the Boyne [...], Co. Louth Ireland. (1790)
A view of Drogheda, across the River Boyne, County Louth, Ireland. To the right of the drawing, one can see the St. Laurence's Gates and the steeple of a church.
Watermark visible l.c.. Title inscribed in ink on verso of drawing.
Irish Topographical Prints & Drawings / Rosalind M. Elmes. - Malton Press, Dublin, 1975
Keywords: Buildings -- Ireland -- Drogheda -- 1790-1800.; Cities & towns -- Ireland -- Drogheda -- 1790-1800.; Rivers -- Ireland -- Drogheda -- 1790-1800.; Steeples -- Ireland -- Drogheda -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.